2010
DOI: 10.1017/s0018246x10000051
|View full text |Cite
|
Sign up to set email alerts
|

Free Trade, Free Labour, and Slave Sugar in Victorian Britain

Abstract: A B S T R A C T. This article reconsiders the sugar duties controversy in early Victorian Britain. Rather than representing the defeat of abolitionism by free trade zeal, the sugar question was a contest of two varieties of anti-slavery thought which had previously co-existed : one believing that slavery's immorality was accompanied by its productive inferiority to free labour and the other asserting that slavery's profits in this world were punished outside the marketplace. West Indian decline after the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The prosperous British West Indies had been wrecked, while all that the abolition of slavery seemed to have done was to shift the places where Britain purchased slave-grown sugar from its own colonies to the flourishing slave colonies of Cuba and Brazil. 88 Events interpreted in this way suggested the folly of adopting twin attacks on the protection of the economy and the protection of slaves. But the timid emancipation settlement of 1833-38 and the seeming failure of emancipation schemes in the older West India colonies of Jamaica and Barbados disenchanted British politicians with what abolition had wrought.…”
Section: Resultsmentioning
confidence: 99%
“…The prosperous British West Indies had been wrecked, while all that the abolition of slavery seemed to have done was to shift the places where Britain purchased slave-grown sugar from its own colonies to the flourishing slave colonies of Cuba and Brazil. 88 Events interpreted in this way suggested the folly of adopting twin attacks on the protection of the economy and the protection of slaves. But the timid emancipation settlement of 1833-38 and the seeming failure of emancipation schemes in the older West India colonies of Jamaica and Barbados disenchanted British politicians with what abolition had wrought.…”
Section: Resultsmentioning
confidence: 99%
“…In 1846, the British government controversially decided to equalize the duties on British colonial and foreign (i.e., slave-grown) sugar (Green 1991 , p. 232; Schuyler 1918 , p. 72). The government did so on the grounds that allowing cheaper slave-produced sugar into the British market would be good for consumers (Huzzey 2010 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, free traders vilified emancipated black Britons as undeserving of special protection, resisting the claims of protectionists that the illegal slave trade would prosper from the measure. 70 This question exposed differing views of the moral geography of Britain's anti-slavery responsibilities. While Bishop Samuel Wilberforce suggested that the consumption of slave-grown commerce would 'plunge this country again into the guilt of this great crime', he was soon disappointed to discover that the rest of the country did not feel the same way.…”
Section: Anti-slavery In One Country?mentioning
confidence: 99%